Pemanfaatan Google Classroom untuk Proses Pembelajaran Siswa Sekolah pada Masa Pandemi Covid-19 - Linda Marlinda; Anton Anton; Frisma Handayanna; Susafa’ati Susafa’ati; Taransa Agasya Tutupoly; Faruq Aziz (LPPM Universitas Nusa Mandiri, 2021)
During the Covid-19 pandemic, the government stopped offline learning and replaced it as distance learning that was done online. This distance learning system is the perfect solution during a pandemic like this time so that permanent teaching and learning activities can be used, well and save students so that they are always at home and minimize the occurrence of Covid-19 transmission. One of these obligations is that the teacher carries out Community Service, this is carried out in relation to the concern of every institution or institution engaged in the field of education, especially Higher Education. Almost all fields are affected by this corona, as well as students and schoolgirls in the Bekasi area, West Java. There are quite a number of students and teachers who have not been able to adapt to the distance learning policy, so this training is held so that teachers and students can make optimal use of the software, especially Google Classroom. At the end of this training, participants can take advantage of and master and know more about online learning with Google Suite, especially the use of Google Classroom. This activity also had a good impact in efforts to increase the penetration of advances in information and communication technology (ICT) for students in Bekasi, this was evident from the positive response they had given during the activity